KARAKTERISTIK BISKUIT COKLAT DARI CAMPURAN TEPUNG PISANG BATU (Musa balbisiana colla) DAN TEPUNG TERIGU PADABERBAGAI TINGKAT SUBSTITUSI - Siti Nurdjanah; Nanti Musita; Dwi Indriani (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
The use of wheat flour as a main ingredient in processed food products in Indonesia will increase the dependence of wheat flour import. This can be reducedpartly by using local foodsource such as balbisiana banana (pisang batu). The purpose of this research was to obtain  formulation of balbisiana banana flour and wheat flour to produce biscuit with the best organoleptic propeties. The experiment was arranged in  a Random Complete Block Design (RCBD) , non factorial with three replications.  The single factor used was the formulation of balbisiana banana flour and wheat, consisted of six levels 90:10 (F1), 85:15 (F2), 80:20 (F3), 75:25 (F4), 70:30 (F5) dan 65 : 35 (F6). The data were analyzed using Barlett test to find homogenity, furthermore the Tuckey test was used to test  the additivity, and then tested using ANOVA.  The mean separation was further analysis using Honest Significant Difference test (HSD) at 5%  level of significance. The results showed that the substitution of  wheat ffour with balbisiana banana flour had significant effect on color, texture, overall acceptance and commercial potential, but i had no significant effect on the taste. The best biscuit was found in  F2 treatment (85% balbisiana banana flour : 15% wheat flour) with the criteria: water , ash, fat, protein, and  , carbohydrate contents were 1,4%, 2,6%, f 20,7%, 5,7%, 69,6% respectively. The  glycemic index (GI) , total dietary fiber and total phenol were 21,1%, 32,3% and 2,8 ppm.